Intracellular β2 integrin (CD11/CD18) interacting partners in neutrophil trafficking. (29th June 2018) - Thome, Sarah; Begandt, Daniela; Pick, Robert; Salvermoser, Melanie; Walzog, Barbara
Abstract: Background: Neutrophil recruitment during acute inflammation critically depends on the spatial and temporal regulation of β2 integrins (CD11/CD18). This regulation occurs by inside‐out and outside‐in signalling via interaction of cytoplasmic proteins with the intracellular domains of the integrin α‐ and β‐subunits. The underlying molecular mechanisms regulating β2 integrins in neutrophils are still incompletely understood. Aim: This review provides a comprehensive overview of our current knowledge on proteins interacting with the cytoplasmic tail of CD18, the conserved β‐subunit of β2 integrins, their regulation and their functional importance for neutrophil trafficking during acute inflammation. Results: A total of 22 proteins including Talin, Kindlin 3 and Coronin 1A have been reported to interact with the CD18 cytoplasmic tail. Here, proteins binding to the cytoplasmic domain of CD18 in experiments using purified, recombinant proteins or peptides in, for example, pull‐down assays, are defined as direct interactors. Proteins that have been shown to interact with the cytoplasmic domain of CD18 using whole cell lysates in, for example, pull‐down experiments are claimed as interacting proteins without evidence for direct interaction. In summary, β2 integrin activation and signalling depend on a specific subset of proteins interacting with CD18 and their precise regulation. If disturbed, profound defects of neutrophil recruitment and activation become evident compromising the innate immune response. Conclusions: The knowledge of proteins interacting with β2 integrins and their regulation during neutrophil trafficking does not only improve our basic understanding of innate immunity but may pave the way to novel therapeutic strategies in the treatment of inflammatory diseases.